Deconstructing Power, Crafting Critical Writers: A Classroom-Based Study on Teaching Animal Farm through Deconstruction - Sunengko, Sunengko; Nurfaisal, Nurfaisal; Firmansyah, Firmansyah; Fitriani, Dina; Edward, Edward (JUPEIS : Jurnal Pendidikan dan Ilmu Sosial, 2025)
This study employed a qualitative textual analysis using Jacques Derrida’s deconstruction approach to examine George Orwell’s Animal Farm. The research aims to uncover how language constructs and destabilizes power relations in totalitarian contexts by analyzing key binary oppositions, such as leader versus people, freedom versus oppression, and justice versus corruption. The analysis reveals that Orwell’s narrative exposes ideological contradictions through slogans like “All animals are equal, but some animals are more equal than others,” illustrating how language manipulation legitimizes political control. The study also highlights how deconstructive reading encourages students to critically interpret textual ambiguities and power structures through reflective writing and classroom discourse. The findings show that integrating deconstruction into literature learning fosters students’ critical thinking and analytical writing skills. This research contributes to literary education by offering a pedagogical framework that promotes deeper engagement with literary texts, enabling students to relate literature to contemporary socio-political realities. It emphasizes the relevance of deconstructive pedagogy in cultivating critical and reflective readers within the framework of 21st-century education.